2021
DOI: 10.3390/w13111546
|View full text |Cite
|
Sign up to set email alerts
|

Application of SWAT in Hydrological Simulation of Complex Mountainous River Basin (Part I: Model Development)

Abstract: The soil and water assessment tool (SWAT) hydrological model has been used extensively by the scientific community to simulate varying hydro-climatic conditions and geo-physical environment. This study used SWAT to characterize the rainfall-runoff behaviour of a complex mountainous basin, the Budhigandaki River Basin (BRB), in central Nepal. The specific objectives of this research were to: (i) assess the applicability of SWAT model in data scarce and complex mountainous river basin using well-established perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…The model is conceptual and computationally efficient, uses readily available inputs and enables users to study long-term impacts [24]. The SWAT is internationally recognized as a solid interdisciplinary watershed-modelling tool with diverse applications [23,25,26,27]. It can be used to simulate a single watershed or a system of multiple hydrologically connected watersheds.…”
Section: Soil and Water Assessment Tool (Swat)mentioning
confidence: 99%
See 1 more Smart Citation
“…The model is conceptual and computationally efficient, uses readily available inputs and enables users to study long-term impacts [24]. The SWAT is internationally recognized as a solid interdisciplinary watershed-modelling tool with diverse applications [23,25,26,27]. It can be used to simulate a single watershed or a system of multiple hydrologically connected watersheds.…”
Section: Soil and Water Assessment Tool (Swat)mentioning
confidence: 99%
“…In the SWAT model, there is a large number of input parameters related to the land use (e.g., SCN curve no) and soil types (e.g., available water capacity of the soil, hydrologic group of soil). A set of model parameters based on the experience from previous studies [2,27,28,32] were carefully selected for the calibration of the model and they are given in Table 6…”
Section: Calibration Parametersmentioning
confidence: 99%
“…Since the hydrological model is able to provide a significant amount of information from limited existing data and identifies the relationship between model parameters and physically observable land surface characteristics, it is the main method currently used for runoff simulation. The three types of hydrological models used in practical applications are the lumped, semi-distributed, and fully-distributed models, which are based on spatial discretization (Marahatta et al, 2021a). For example, Génie Rural à four paramètres Journalier (GR4J), Hydrologiska Byråns Vattenbalansavdelning (HBV) and a simplified version of the HYDROLOG (SIMHYD) are lumped models, while topographic hydrologic model (TOPMODEL), Variable Infiltration Capacity (VIC) and the SWAT are semidistributed models.…”
Section: Introductionmentioning
confidence: 99%
“…The size and structure of watersheds as well as their topographic and geographic structures vary significantly due to geological, morphological, vegetation, soil, and climatic differences (Loukas & Vasiliades, 2014, Marahatta et al, 2021. In response to human development, fast climate dynamics, and slow geologic processes, there has been a reciprocal evolution within catchments resulting in changes in the soils, vegetation, and topography, mediated by material and energy fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…The SWAT (Soil and Water Assessment Tool) is an open-source distributed model (Arnold et al, 1998 that has a large and growing application in the hydrological characterizing of catchments (Asurza & Lavado, 2020). Regarding previous studies, the tool has shown strength in discharge estimation in mountainous catchments (Koycegiz & Buyukyildiz, 2019, Luo et al, 2011, Marahatta et al, 2021, Yacoub & Foguet, 2013. The model has successfully been used to estimate flow rates on a wide scale and in various hydrological regions.…”
Section: Introductionmentioning
confidence: 99%